Facile one-pot synthesis of a porphyrin-based hydrophilic porous organic polymer and application as recyclable absorbent for selective separation of methylene blue. (December 2018) - Liu, Tingting; Jing, Lu; Cui, Lin; Liu, Qingyun; Zhang, Xiaomei
Abstract: With the development of dye production and printing industry, dyes wastewater has increased dramatically. The resulting environmental pollution problem is increasing seriously. In the present work, a porphyrin-based porous organic polymer (PPOPs-OH) was synthesized by using pyrrole and 2, 6-dihydroxynaphthalene-1, 5-dicarbaldehyde (DHNDA) as basic building block in situ. This method was cost- and time-efficient, without the participation of metal catalysts. Further reaction of PPOPs-OH with chlorosulfonic acid, a new sulfonic acid functional material (PPOPs-SO3 H) was obtained with the increasing electronegativity and hydrophilicity. PPOPs-SO3 H exhibit good adsorption capacity for methylene blue (MB) from water (980.4 mg g −1 ) and excellent selectivity for MB in the present of rhodamine B (RhB) and methyl orange (MO). Mechanism investigation revealed that electrostatic in comparison with π-π interaction is the prominent force in the absorption process. Recycling experiments found the absorption properties of PPOPs-SO3 H did not reduce significantly after several cycles. As a consequence, our findings highlight an appealing opportunities for covalent organic polymers with their potential application as high-efficiency and robust adsorbents for pollutants removal and environmental protection. Graphical abstract: POPs-SO3 H obtained by facile one-pot synthesis exhibited excellent adsorption performance towards MB, and its maximum adsorption capacity is 980.4 mg g −1 . Highlights: PPOPs-SO3 H was obtained by cost- and time-efficient method. PPOPs-SO3 H exhibit good adsorption ability for methylene blue and well selectivity. MB adsorption kinetics and mechanism were investigated. PPOPs-SO3 H showed excellent sustainability and recyclability for dye removal. PPOPs-SO3 H possessed a applicability for wastewater treatments.